2015
DOI: 10.4103/1319-3767.161643
|View full text |Cite
|
Sign up to set email alerts
|

Framework for interpretation of trypsin-antitrypsin imbalance and genetic heterogeneity in pancreatitis

Abstract: Early intracellular premature trypsinogen activation was interpreted as the key initiator of pancreatitis. When the balance in the homeostasis of trypsin and antitrypsin system is disequilibrated, elevated aggressive enzymes directly attack the pancreatic tissue, which leads to pancreatic destruction and inflammation. However, trypsin alone is not enough to cause complications in pancreatitis, which may play a crucial role in modulating signaling events in the initial phase of the disease. NFκB activation is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 91 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Obliterative vasculitis and a high level of α-1-AT expression were also observed in the patients enrolled in the present study. Fibrosis and vasculitis induced by trypsin-antitrypsin imbalance have been reported in immune systemic disorders, including inflammatory bowel disease ( 22 ) and hepatic fibrosis ( 23 ), and as a key initiator in IgG4-related pancreatitis ( 24 ). In addition, it has been observed that mutations in protease serine 1 cause ectopic trypsinogen activation, and calcitonin gene-associated peptide-β splice region pathogenic variants may lead to plasma cell neurotropic enrichment, inducing obliterative vasculitis and perineural inflammation in the pancreas in type 1 AIP ( 6 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obliterative vasculitis and a high level of α-1-AT expression were also observed in the patients enrolled in the present study. Fibrosis and vasculitis induced by trypsin-antitrypsin imbalance have been reported in immune systemic disorders, including inflammatory bowel disease ( 22 ) and hepatic fibrosis ( 23 ), and as a key initiator in IgG4-related pancreatitis ( 24 ). In addition, it has been observed that mutations in protease serine 1 cause ectopic trypsinogen activation, and calcitonin gene-associated peptide-β splice region pathogenic variants may lead to plasma cell neurotropic enrichment, inducing obliterative vasculitis and perineural inflammation in the pancreas in type 1 AIP ( 6 , 25 ).…”
Section: Discussionmentioning
confidence: 99%